Pengaruh Penggunaan Media Animasi Powtoon Dalam Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Matematika Siswa Kelas X MIA SMA Negeri 1 Tapung - Sri Rahma Jelita; Alzaber Alzaber; Mefa Indriati (UIR Press, 2023)
This study aims to determine the effect of the use of powtoon animation media in the STAD type cooperative learning model on the mathematics learning outcomes of class X MIA students at SMA Negeri 1 Tapung. This research is a quasi-experimental research (quasi-experimental) starting on May 16 2023 to May 26 2023, with a nonequivalent control group design using a purposive sampling technique. This research was conducted for five meetings. The population in this study were all students of class X MIA SMA Negeri 1 Tapung. Data collection techniques in this study were carried out using test and documentation techniques. As for the instrument for collecting data on learning outcomes through pretest and posttest which will be processed using descriptive analysis and inferential analysis. After processing the data, the results of this study with descriptive analysis and inferential analysis showed that there was an influence of the STAD type cooperative learning model on the experimental class. Based on the results of this study, it can be concluded that there is an influence of the STAD type cooperative learning model on the mathematics learning outcomes of class X MIA students of SMA Negeri 1 Tapung.